2014
DOI: 10.1051/0004-6361/201322448
|View full text |Cite
|
Sign up to set email alerts
|

Formation of phase lags at the cyclotron energies in the pulse profiles of magnetized, accreting neutron stars

Abstract: Context. Accretion-powered X-ray pulsars show highly energy-dependent and complex pulse-profile morphologies. Significant deviations from the average pulse profile can appear, in particular close to the cyclotron line energies. These deviations can be described as energy-dependent phase lags, that is, as energy-dependent shifts of main features in the pulse profile. Aims. Using a numerical study we explore the effect of cyclotron resonant scattering on observable, energy-resolved pulse profiles. Methods. We ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…5). Although the feature is marginally significant, we observe that a similar behaviour has also been observed in other sources and can be associated with change of the pulsar beam pattern around the resonance energy (Ferrigno et al 2009;Schönherr et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…5). Although the feature is marginally significant, we observe that a similar behaviour has also been observed in other sources and can be associated with change of the pulsar beam pattern around the resonance energy (Ferrigno et al 2009;Schönherr et al 2014).…”
Section: Discussionsupporting
confidence: 85%
“…The pulse map shows that the secondary peak starts to form at ∼6 keV and is of comparable strength to the main peak above ∼15 keV. Interestingly, we do not find any significant phase shifts around the cyclotron line energy as predicted by theory (Schönherr et al 2014) and as observed in 4U 0115+634 by Ferrigno et al (2011).…”
Section: Timing Analysissupporting
confidence: 68%
“…Another peculiar effect has been observed in the pulse profiles of some X-ray pulsars: the pulse profile shifts in phase at the energy of the CRSFs (e.g., in 4U 0115+63; Ferrigno et al 2011). This can be explained by the different cross sections at the CRSF energies, leading to changes in emission pattern, as calculated by Schönherr et al (2014).…”
Section: Cyclotron Line Parameters As Function Of Pulse Phasementioning
confidence: 99%